Herbaria collections as cues of leaf trait adjustments in Senecio pyrenaicus subsp. carpetanus in response to environmental aggravation. - Magaña Ugarte, Rosina (Mediterranean Botany, 2022)
The direct link of stomatal traits to fundamental physiological processes makes them critical attributes for defining leaves’ physiological potential. Stomatal traits can serve as proficient ecophysiological proxies of plant responses to changing environments. Studying stomatal patterns and structures in leaves could be a particularly suitable approach to assess plant responses to the current climate crisis imperiling our ecosystems. The reconstruction of plant responses to past conditions could be attained by assessing stomatal and other foliar traits from preserved specimens in herbarium collections associated with primary strategies (i.e., growth, resource gaining, water usage). In combination with climatic records, studying these traits offers a promising and rarely explored venue in the context of changing climate. The assessment of herbarium specimens offers a powerful tool to reproduce long-term trait variations along shifting climates when monitoring programs are inexistent. This research aims to unveil the great potential in-built in herbaria specimens to discern long-term feedbacks at various scales (morphologic, physiologic) in the high-mountain herb Senecio pyrenaicus subsp. carpetanus. The latter to foresee its enduring capacity to the challenging conditions during its growing season in Sierra de Guadarrama and their expected aggravation due to the ongoing climate crisis. Analysis of conserved and recent specimens revealed S. carpetanus could adjust to the shift to drier growing seasons in these mountains and the aggravating climate over the last three decades by modifying leaf micromorphological traits (i.e., smaller, densely packed stomata) and leaf size. Additionally, these results suggest a potential influence of the reportedly increasing O3 levels in the study site on the observed increases in stomatal density and reduced stomatal size. These findings point out a potential improvement in the control of stomatal aperture and in minimizing the incoming rates of O3 to plant cells. Overall, this research expects to draw attention to the valuable evidence in herbaria collections to assess plant distribution variations, morphology, and phenology across spatial and time scales. Similarly, it intends to open the gate for future studies incorporating herbaria collections to evaluate plant responses and predict their ensuing fitness under changing environmental conditions.